Pengaturan Orientasi Posisi Objek pada Proses Rapid Prototyping Menggunakan 3D Printer Terhadap Waktu Proses dan Kwalitas Produk - Sobron Lubis; David Sutanto (Institute of Research and Community Outreach, Petra Christian University, 2014)
Rapid prototyping can be defined as the methods used to create a scale model (prototype) from the start part of a product (part) or assembly (assembly) quickly by using the data of computer aided design (CAD) three dimensional. In the process of printing 3D objects setting is crucial to product quality and processing time is done. This research was conducted with the object orientation variation in the vertical and horizontal of the two types of polymer material ABS and PLA in order to determine the processing time and product quality. This research was carried out by using a printer 3D. From this study showed that the process of making specimens for PLA and ABS material selection object orientation in horizontal position produces a shorter process time and surface condition of surface roughness values ​​are smaller than the vertical orientation position.